2011
DOI: 10.2174/1874407901105010049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Kaolin Particle Film Formulation Against Populations of the Aphid Lipaphis erysimi Kalt. (Homoptera: Aphididae) in Cabbage

Abstract: Abstract:Infestations of the aphid Lipaphis erysimi Kalt.cause a mean yield loss of cabbage that varies from 35.4% to 73.3% depending from agro-climatic conditions. To control this pest insect in Sub-saharan Africa, synthetic chemical insecticides are usually applied. Kaolin is a white, non-abrasive, inert aluminosilicate mineral that has been shown to effectively protect host plants from insect pests including lepidopterans, sucking insects and mites. The present work is aimed to study the effects of kaolin o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…Cabbage is prone to multiple pests and diseases. Cabbage whitefly, aphids, and mites are considered as destructive pests which reduce the yield significantly (Trdan and Papler 2002;Antonious et al 2007;Alavo and Abagli 2011;Richter and Hirthe 2014). Spiromesifen could be used for control of these pests (Marcic et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Cabbage is prone to multiple pests and diseases. Cabbage whitefly, aphids, and mites are considered as destructive pests which reduce the yield significantly (Trdan and Papler 2002;Antonious et al 2007;Alavo and Abagli 2011;Richter and Hirthe 2014). Spiromesifen could be used for control of these pests (Marcic et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The technology of mineral particle films is a potential alternative to some insecticides in the control of different pests (Alavo and Abagli 2011). Kaolin is mineral composed of aluminum silicate (Al 4 Si 4 O 10 (OH) 8 ) of fine grain, white color, flat, porous, and non-expanding, dissolving in water and chemically inert at a wide range of pH (Harben 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies have shown that kaolin has a deterrent effect on the feeding and oviposition behaviors of the boll weevil (Showler 2002), although the effectiveness of this product may be specific to some species of insects and must be studied for each pest in their own environment (Glenn and Puterka 2005). Kaolin has been shown to be effective against aphids (Cottrell et al 2002;Wiss andDaniel 2004, Alavo andAbagli 2011); beetles (Showler 2002); fruit flies (Mazor and Erez 2004;Lo Verde et al 2011), psyllids, leafhoppers and mites in various cropping systems (Puterka et al 2000;Peng et al 2011). The mechanisms of action of kaolin against (excluded targeted) insect pests include repellency, tactile or visual cue interference, impairment or disruption of oviposition and feeding activity, and decreased longevity and survivorship (Glenn and Puterka 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Kaolinin birçok bitkide zararlılara karşı da etkili olduğu belirlenmiştir. Armutlarda psillid [17], soğanlarda trips [18], pamukta pamuk kurdu [19], turunçgillerde Akdeniz meyve sineği [20], lahanada yaprakbiti [21] zararını azalttığı bildirilmektedir.…”
Section: Introductionunclassified